Factors causes abandoned housing projects: case study in Klang - Azhar, Nur Amira (2024)
The rising number of abandoned housings in Malaysia has causes many problems. This issue not only occur in Malaysia but also in other country. Thus, the purpose of this paper is determining the factors causes abandoned housing projects in Klang, Selangor. This research only limited to housing project scheme, building other than housing will be excluded from this research and focus on registered estate agent, registered valuer including valuer and estate agent. In this research there are 2 objectives that had been identified which are to determine the factors of abandon housing projects and to rank the factors that contribute to abandoned housing projects. Primary and secondary data collection was used for this study. The primary data was for data collection to ask question about the factor causes abandoned housing projects while secondary data is to find the data about the number of abandoned housing projects in government official website, article and journal. Data collection was analyse using SPSS. This software use to analyse the statistical data. The research used purposive sampling method as the target respondent will be registered valuer, registered estate agent, valuer and estate agent. The estimated sampling for this research was 28 respondents as the total respondent was 30 company in Klang. Data and findings were represented in table and pie charts for each question. The findings found that the factors cause most significant to abandoned housing project are mismanagement, financial issue, environmental impact issue, law issue, construction issue and political issue. The most factors that contributed to abandoned housing project in Klang is financial issue, 4.43.